2012
DOI: 10.1177/030089161209800616
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Computed Tomography-Guided Lung Biopsies: Preliminary Results using an Augmented Reality Navigation System

Abstract: The augmented reality navigation system used in this study was a highly safe, technically reliable and effective support tool in percutaneous CT-guided lung biopsy, allowing to shorten the procedure time and reduce the incident x-ray radiation dose to patients and the rate of insufficient specimens. Furthermore, it has the potential to increase the number of procedures executed in the allocated time without increasing the number of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Our results are consistent with previous reports in terms of diagnostic success for PLB [ 20 ]. In a study, which included 180 patients, Grasso et al found a diagnostic success rate of 96% in the navigation group and 90% in the standard group [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are consistent with previous reports in terms of diagnostic success for PLB [ 20 ]. In a study, which included 180 patients, Grasso et al found a diagnostic success rate of 96% in the navigation group and 90% in the standard group [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…The automatic recording and detection of the magnetic transmitter on the patient’s skin has always been effective and has never prevented the use of the navigation system. In a randomized study on 180 patients using a navigation system based on optical tracking in the field of lung biopsies, Grasso et al found a significant reduction in the procedure time, the number of control scans and the radiation dose [ 20 ]. In another study, this optical navigation system called SIRIO (MASMEC S.p.A., Modugno, BA, Italy) has been shown to be more accurate for percutaneous lung biopsies of lesions <20 mm [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of questionnaire evaluation and electromyography test indicate that ARG can help correct surgeons' poor posture during video-assisted surgery and reduced muscular fatigue of the upper body. More than this, AR performed a good value in the lesion-navigation system (32,48,49) and multi-center joint surgery virtual system (50).…”
Section: Ar Technologymentioning
confidence: 97%
“…AR systems map cross-sectional data onto the subject's body; therefore, the interventional operator can visualize the anatomic structures inside the patient. Preclinical investigations have documented the applicability of AR systems for interventional procedures guided with magnetic resonance imaging (3-9), ultrasonography (10,11), and CT (12,13), and early clinical investigations have begun (14). Because the AR described in our study is video based, its use instead of fluoroscopy during cone-beam CT -guided procedures results in a reduction in radiation dose.…”
Section: Discussionmentioning
confidence: 90%